2019
DOI: 10.1002/cphc.201801037
|View full text |Cite
|
Sign up to set email alerts
|

Interrogation of the Effect of Polymorphism of a Metal‐Organic Framework Host on the Structure of Embedded Pd Guest Nanoparticles

Abstract: Metal‐organic frameworks (MOFs) are very promising host materials for nanoscale guest materials. However, some MOFs such as MIL‐53 are known to undergo phase transitions which can complicate the guest particle size control. In this study, Pd nanoparticles embedded in Al‐MIL‐53 were synthesised via (a) electrodeposition and (b) gas‐phase reduction. A thorough structural investigation revealed that each synthesis method most likely favoured a different phase of Al‐MIL‐53, presenting the possibility of MOF phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…The TEM images and XRD of the used I–H Au@UiO-66 catalyst revealed that after five catalytic cycles no Au particle agglomerations could be observed, and UiO-66 retained its crystalline structure (Figure A­(f) and Figure B­(h)). Another example that highlights the importance of the synthetic method was shown by Butson et al The researchers demonstrated that MOFs featuring the pore breathing effect could possibly exhibit a preferential phase behavior for nanoparticles obtained by different reduction methods. This effect was shown with MIL-53­(Al), which is known for its breathing phenomenon.…”
Section: Mofs As Supports For Metal Nanoparticlesmentioning
confidence: 99%
“…The TEM images and XRD of the used I–H Au@UiO-66 catalyst revealed that after five catalytic cycles no Au particle agglomerations could be observed, and UiO-66 retained its crystalline structure (Figure A­(f) and Figure B­(h)). Another example that highlights the importance of the synthetic method was shown by Butson et al The researchers demonstrated that MOFs featuring the pore breathing effect could possibly exhibit a preferential phase behavior for nanoparticles obtained by different reduction methods. This effect was shown with MIL-53­(Al), which is known for its breathing phenomenon.…”
Section: Mofs As Supports For Metal Nanoparticlesmentioning
confidence: 99%
“…Besides the structural states of the frameworks and their components, real-space studies have flourished in helping to verify and elucidate the mechanisms of functionalization processes. PDFs are uniquely sensitive for identifying the presence, site-isolation, and structural states of species added into the pores and/or bound to coordinatively unsaturated sites on the clusters (see section for more details), for instance by gas and liquid adsorption, atomic layer deposition, , ligand exchange, nanocasting, and the incorporation or nucleation of larger complexes and nanoparticles. , These processes will be especially important for enabling applications in gas loading/storage, remediation, catalysis, and more. Further effects on the structural state of the framework have been investigated due to electrochemical cycling for battery applications and degradation, , and due to in situ loading and detoxification of chemical warfare agent simulants …”
Section: Applicationsmentioning
confidence: 99%
“…104 A number of questions as for how the synthesis method, the porosity and the nature of the metal affect nanoparticle formation, location and dispersion, remain open. [105][106][107][108][109][110] It is worth mentioning that Pd is by far the most studied metal for these kind of composites, given its use both for catalytic applications (e.g., hydrogenations, oxidations and C-C coupling) and energy or hydrogen storage. A detailed description on these issues, and more specifically, of the uses in catalysis of metallic nanoclusters and nanoparticles embedded in MOFs is presented in Section 1.4.2.…”
Section: Defects and Disorder In Metal-organic Frameworkmentioning
confidence: 99%